STRATEGI PENGEMBANGAN USAHA AIR MINUM DALAM KEMASAN (Studi Kasus PT. Govinda Tirta, Nyanglan Bangli) - Ferry Artha Yoga, I Wayan; Wrasiati, Luh Putu; Ganda Putra, Gusti Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 4 (2016): Desember, 2017)
This study aimed  (1)  to  analyze the internal and external conditions  of PT. Govinda Tirta, (2)  to develop and recommend business development strategies  and (3) to finding the priority  strategies  of PT. Govinda Tirta.  The analysis of  Business Development  Strategies  used a  matrix of Strength, Weakness, Opportunities  and Threats (SWOT), supported by the analysis of quantitative uses a matrix of External Factor Evaluation (EFE), Internal Factor Evaluation (IFE), Internal External (IE) and Quantitative Strategic Planning Matrix (QSPM). The results showed that the weighting and rating value  of  IFE  matrix  was 3.2 indicated strong positions and  EFE Matrix  was 3.29  indicated a strong ability. In  IE matrix, the strategy that must be done was to grow and develop a strategy, which consists f an intensive strategies  (market penetration, market development and product development), and integrative strategies (backward integration, forward integration and horizontal integration). There were 8 alternative strategies that can be structured  to develop businesses of PT. Govinda Tirta. The highest Total Atractive Score value of alternative strategies was promoting with IT based. Keywords:  Business Development Strategies, Bottled Water, PT. Govinda Tirta, SWOT, QSPM
Keywords: 116